Transshipment site selection using the AHP and TOPSIS approaches under fuzzy environment - Onut, Semih; Soner, Selin (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
Site selection is an important issue in waste management. Selection of the appropriate solid waste site requires consideration of multiple alternative solutions and evaluation criteria because of system complexity. Evaluation procedures involve several objectives, and it is often necessary to compromise among possibly conflicting tangible and intangible factors. For these reasons, multiple criteria decision-making (MCDM) has been found to be a useful approach to solve this kind of problem. Different MCDM models have been applied to solve this problem. But most of them are basically mathematical and ignore qualitative and often subjective considerations. It is easier for a decision-maker to describe a value for an alternative by using linguistic terms. In the fuzzy-based method, the rating of each alternative is described using linguistic terms, which can also be expressed as triangular fuzzy numbers. Furthermore, there have not been any studies focused on the site selection in waste management using both fuzzy TOPSIS (technique for order preference by similarity to ideal solution) and AHP (analytical hierarchy process) techniques. In this paper, a fuzzy TOPSIS based methodology is applied to solve the solid waste transshipment site selection problem in Istanbul, Turkey. The criteria weights arc calculated by using the AHP. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: GROUP DECISION-MAKING; WASTE MANAGEMENT; AREA; ALGORITHM; SYSTEMS; Engineering; Environmental Sciences & Ecology